Poppers, by Inducing HHV-8 Virion Production, Can Act as a Promoter for HHV-8 Transmission in Men Who Have Sex With Men. (31st March 2021) - Jary, Aude; Gothland, Adélie; Palich, Romain; Leducq, Valentin; Monsel, Gentiane; Imbert, Sébastien; Schneider, Luminita; Simon, Anne; Spano, Jean-Philippe; Katlama, Christine; Larabi, Islam Amine; Alvarez, Jean-Claude; et al.
Abstract: Environmental factors were reported to increase the risk of human herpesvirus 8 (HHV-8) transmission. In a population of men who have sex with men (MSM), we found evidence that chemsex was associated with human herpesvirus 8 seropositivity in vivo and that poppers induced HHV-8 virion production in vitro. Our finding may explain the higher HHV-8 transmission in MSM.